Antecedents of tax compliance of small and medium-sized enterprises (smes): the perspective of tamale metropolis - Abdul Razak Usamah (KNUST, 2024)
A thesis submitted to the department of accounting and finance, kwame nkrumah university of science and technology, in partial fulfilment of the requirements for the award of master of science (accounting & finance)